Engineering light-inducible nuclear localization signals for precise spatiotemporal control of protein dynamics in living cells - Niopek, Dominik; Rönsch, Julia; Dräbing, Thomas; Wehler, Pierre; Eils, Roland; Di Ventura, Barbara (Nature Communications, 2014)
The function of many eukaryotic proteins is regulated by highly dynamic changes in their nucleocytoplasmic distribution. The ability to precisely and reversibly control nuclear translocation would, therefore, allow dissecting and engineering cellular networks. Here we develop a genetically encoded, light-inducible nuclear localization signal (LINuS) based on the LOV2 domain of Avena sativa phototropin 1. LINuS is a small, versatile tag, customizable for different proteins and cell types. LINuS-mediated nuclear import is fast and reversible, and can be tuned at different levels, for instance, by introducing mutations that alter AsLOV2 domain photo-caging properties or by selecting nuclear localization signals (NLSs) of various strengths. We demonstrate the utility of LINuS in mammalian cells by controlling gene expression and entry into mitosis with blue light.
Gesehen am 11.08.2020